Fuzzy Annihilator Ideals of C-Algebra. (10th September 2021) - Norahun, Wondwosen Zemene; Alemayehu, Teferi Getachew; Addis, Gezahagne Mulat
Abstract : In this paper, we introduce the concept of relative fuzzy annihilator ideals in C -algebras and investigate some its properties. We characterize relative fuzzy annihilators in terms of fuzzy points. It is proved that the class of fuzzy ideals of C -algebras forms Heything algebra. We observe that the class of all fuzzy annihilator ideals can be made as a complete Boolean algebra. Moreover, we study the concept of fuzzy annihilator preserving homomorphism. We provide a sufficient condition for a homomorphism to be a fuzzy annihilator preserving.